Integrating Big Data Technologies to Strengthen Network Security Awareness - Hariguna, Taqwa (International Journal of Informatics and Information Systems, 2022)
The Network Security Alarm Warning System (NSAWS) is a sophisticated, real-time, large-scale database management system designed to enhance cybersecurity by analyzing user identity data and access rights within the amassed information to detect potential threats and issue timely alarm notifications. This paper explores methods to bolster network attack prevention in a Big Data framework, starting with an overview of prevalent internet technologies in our country and their current applications. It then elaborates on the architecture, deployment strategies, and operational methodologies of the NSAWS, emphasizing the integration of fundamental security infrastructures like cloud computing platforms and firewalls. Following this, the traditional NSAWS is analyzed, and a simulation platform is tested to evaluate its performance in identifying and alerting network security threats. The results indicate that the NSAWS platform demonstrates exceptional accuracy and stability in its warning capabilities, effectively safeguarding network security by swiftly addressing potential vulnerabilities and threats. This paper underscores the importance of leveraging advanced technologies and robust security frameworks to fortify network defenses against evolving cyber threats, highlighting the NSAWS as a vital tool in maintaining and enhancing network security in an increasingly digital and interconnected world.